2019
DOI: 10.1167/iovs.19-26844
|View full text |Cite
|
Sign up to set email alerts
|

Choroidal Microvascular Dropout in Pseudoexfoliation Glaucoma

Abstract: PURPOSE. To compare the prevalence of choroidal microvasculature dropout (CMvD) in pseudoexfoliation glaucoma (PXG) and disease severity-matched primary open-angle glaucoma (POAG) eyes. METHODS. In a cross-sectional study, 39 eyes with PXG (33 patients) and 39 glaucoma severitymatched POAG eyes (34 patients) underwent visual fields, optical coherence tomography and optical coherence tomography angiography examination. Peripapillary vessel density (VD) was evaluated from the radial peripapillary capillary slab,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 27 publications
2
7
1
Order By: Relevance
“…Previous studies have examined patients with XFG and POAG to assess the OCTA-based macular (7,11) and peripapillary (5,12-14) regions individually and together (9,(15)(16)(17)(18). Some of the results are consistent with our current research (11,12,14,17).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Previous studies have examined patients with XFG and POAG to assess the OCTA-based macular (7,11) and peripapillary (5,12-14) regions individually and together (9,(15)(16)(17)(18). Some of the results are consistent with our current research (11,12,14,17).…”
Section: Discussionsupporting
confidence: 90%
“…Some of the results are consistent with our current research (11,12,14,17). Several of these studies recorded observations once daily (11)(12)(13)(14)16,18), while a few used multiple observations, ranging from 2 to 5 per day. Considerable reduction in retinal VD in XFG eyes has been reported by some researchers (11)(12)(13), while others did not find a difference between the retinal VD assessments of XFG and POAG eyes (15).…”
Section: Discussionsupporting
confidence: 89%
“…The contrast between our results and those of aforementioned studies might result from disease severity discrepancies of the eyes included in the studies; that is, we only enrolled eyes with very early-stage disease. However, a recent study by Pradhan et al, which compared severity-matched 39 eyes with XFG and 39 eyes with POAG, found no significant difference in peripapillary VD (4.5 × 4.5) of the RPC in contradiction to previous studies (28) . Another factor that might explain the difference between the results of these studies and those of our study is the size and resolution of the area captured on OCT-A, which was 3 × 3 mm (higher definition) in our study.…”
Section: Discussionmentioning
confidence: 72%
“…Park et al (51) found reduced superficial peripapillary vessel density in the inferonasal and nasal sectors of eyes with XFG compared to POAG. Two recent studies showed that XFG eyes had a similar level of peripapillary and superficial macular vessel densities compared with open angle glaucoma eyes (52,53).…”
Section: Peripapillary Vessel Involvement In Different Types Of Glaucomamentioning
confidence: 99%